Digestibility of the lichen Stereocaulon paschale in reindeer - Jacobsen, Endre (Rangifer, 1981)
The digestibility of the lichen Stereocaulon paschale is studied in a digestibility trial with two reindeer calves. The lichen is collected near Kautokeino in Northern Norway. Chemical composition of the lichen is shown in Table 1. Compared with Cladonia-species the content of crude protein and ash is higher in Stereocanlon paschale The content of Ca, P and Mg in the two species is of the same magnitude, while the content of Na and CI is ten times higher in Cladonia alpestris. The estimated digestibility is shown in Table 2. The dry matter digestibility is calculated to 46, 4%, which is very low compared to Cladonia-species. The higher crude protein content in Stereocaulon paschale has resulted in a positive apparent digestibility of protein.Tinajåkålån (Stereocanlon paschale) sulavuus porolla.Abstract in Finnish / Yhteenveto: Tinajåkålån sulavuutta on tutkittu sulavuuskokeissa kahdella poronvasalla. Kokeessa kåytetty jåkålå on koottu låheltå Kautokemoa. Jåkålån kemiallinen koosturnus on esitetty taulukossa I. Tinajåkålån sisåltåmå raakaproteiini- ja tuhkapitoisuus on korkeampi kuin (Cladonia-lajeilla). Ca-, P- ja Mg-pitoisuudet ovat po. jåkålålajeilla samantasoiset, kun taas Cladonia alpestris sisaltåmåt Na- ja Cl-pitoisuudet ovat kymmenen kertaa korkeampia. Sulavuuslaskelmat esitetåån taulukossa 2. Kuiva-aineen sulavuus on 46,4% mikå on erittåin alhainen verrattuna Cladonia-lajien sulavuuteen. Tinajåkålån korkeampi proteiinisisålto on vaikuttanut myonteisesti valkuaisaineen sulavuuteen.Fordøyelighet av saltlav, (Stereocaulon paschale) til reinAbstract in Norwegian / Sammendrag: Fordøyeligheten av saltlav (Stereocaulon paschale) er undersøkt i fordøyelsesforsøk med 2 reinkalver. Lav til forsøket er sanket nær Kautokeino. Kjemisk sammensetning av lavet er vist i Tabell 1. Sammenlignet med Cladonia-arter er innholdet av råprotein og aske høyere i saltlavet. Innholdet av Ca. P og Mg er på samme nivå i disse arter, mens innholdet av Na og Cl er ti ganger høyere i Cladonia alpestris. Den beregnede fordøyelighet er vist i Tabell 2. For tørrstoff er fordøyeligheten 46,4%, som er svært lavt sammenlignet med fordøyeligheten for Cladonia-arter. Det høyere proteininnholdet i saltlav har ført til positiv fordøyelighet for protein.